Study of some Biological and Ecological aspects of the fly Chrysomya albiceps (WIEDEMANN)(DIPTERA; CALLIPHORIDAE) - Suhad Y. Jassim; Razzaq sh. Augul (مجلة جامعة الانبار للعلوم الصرفة, 2012)
The effects of temperature on some biological aspects of Chrysomya albiceps (Wied.) were studied. The incubation, larval and pupation periods as well as mortality were calculated at constant temperature and relative humidity. The temperature 30Co was preferable to egg and larval stages, whereas the 32Co was preferred for pupal stage.Sex-ratio was affected by temperature, the results declared that male emergence of high rate compared with the female in each treatment, but this rate decreased gradually with the increase of temperature.The adults which were reared at laboratory temperature of 24Co appeared to have increased longevity in both sexes, but the female did not deposit egg ; while 30 Co was preferable for fly for egg deposition.